1985
DOI: 10.1021/bk-1985-0286.ch024
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Cationic Polymerization of Limonene Oxide, α-Pinene Oxide, and β-Pinene Oxide

Abstract: After suitable drying, the subject monomers in the form of neat liquids undergo radiation-induced poly merization with no apparent side reactions and high conversions to precipitatable polymers of low molec ular weight. A high frequency of chain (proton) transfer to monomer is indicated by the fact that the kinetic chain lengths are estimated to be several hundred times larger than the range of DP n values (12-4). Structural characterization of the limonene oxide polymer by 1 H and 13 C NMR spectroscopy provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…The mono-epoxidation leads to limonene oxide ( E4 ), while the oxidation of both double bonds gives limonene dioxide ( E4a ). The limonene derivatives E4 and E4a can be used as monomers in the polymer industry. , A huge amount of catalytic systems have been developed for the epoxidation of A4 to E4 or E4a , mostly with H 2 O 2 , which include heterogeneous catalysts based on Co, Mn, Ru, Mo, Re, Fe, polyoxometalates, and Ti-substituted zeolites (Scheme ). …”
Section: Cyclic Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…The mono-epoxidation leads to limonene oxide ( E4 ), while the oxidation of both double bonds gives limonene dioxide ( E4a ). The limonene derivatives E4 and E4a can be used as monomers in the polymer industry. , A huge amount of catalytic systems have been developed for the epoxidation of A4 to E4 or E4a , mostly with H 2 O 2 , which include heterogeneous catalysts based on Co, Mn, Ru, Mo, Re, Fe, polyoxometalates, and Ti-substituted zeolites (Scheme ). …”
Section: Cyclic Ethersmentioning
confidence: 99%
“…The limonene derivatives E4 and E4a can be used as monomers in the polymer industry. 358,359 A huge amount of catalytic systems have been developed for the epoxidation of A4 to E4 or E4a, mostly with H 2 O 2 , which include heterogeneous catalysts based on Co, Mn, Ru, Mo, Re, Fe, polyoxometalates, and Ti-substituted zeolites (Scheme 52). 360 In 2009, Ding and co-workers reported the conversion of A4 with H 2 O 2 in the presence of a tungsten-based polyoxometalate catalyst, giving epoxide E4 in 98% yield.…”
Section: Dimethyl Carbonate (C1) Dimethyl Carbonate (Dmc C1mentioning
confidence: 99%
“…Likewise, limonene has been radically copolymerized by Sharma and Srivastava with styrene, methyl methacrylate, acrylonitrile, N -vinylpyrrolidone, and other comonomers . Regarding the polymerization of terpene derivatives, Aikins and Williams reported the radiation-induced cationic polymerization of limonene oxide, α-pinene oxide, and β-pinene oxide, which led to low molecular weight polyethers with high monomer conversions . More recently, Coates and co-workers reported the syntheses of alternating polycarbonate copolymers of ( R )-limonene oxide and carbon dioxide using β-diiminate zinc complexes .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45] In a previous study, Aikins and Williams (1981) reported on the radiation-induced cationic polymerization of neat LO at room-temperature by ring-opening of the epoxide moiety yielding a low molecular weight 1,2-trans polyether (7.6 < DP < 18.7) accompanied by very high monomer conversions into polymer (at least 80%). 46 Duchateau and co-workers (2013) synthesized partially bio-based alternating polyesters by catalytic ring-opening copolymerization of LO and phthalic anhydride via a series of metal t-Bu-salophen complexes combined with different cocatalysts and various mono-/di-/tri-functional chain-transfer agents (CTA)s. Chromium-chloride based catalysts provided the best results without any major drop in catalytic activity. Inclusion of (CTA)s enabled molecular weight reduction of the copolymers while retaining low polydispersities.…”
Section: Introductionmentioning
confidence: 99%